2021
DOI: 10.3390/cancers13133224
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Triggered Resolvin D1 Reduces Proliferation and the Neutrophil to Lymphocyte Ratio in a Mutant KRAS-Driven Lung Adenocarcinoma Model

Abstract: Tumour-associated neutrophils (TANs) can support tumour growth by suppressing cytotoxic lymphocytes. AT-RvD1 is an eicosanoid that can antagonise neutrophil trafficking instigated by ALX/FPR2 ligands such as serum amyloid A (SAA). We aimed to establish whether SAA and ALOX5 expression associates with TANs and investigate the immunomodulatory actions of AT-RvD1 in vivo. MPO-positive neutrophils were quantified in tumour blocks from lung adenocarcinoma (n = 48) and control tissue (n = 20) by IHC. Tumour expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…Therefore, an impairment in the RvD pathway (biosynthesis and signaling) could be detrimental in cancer, since it is linked to poorer prognosis and associated with a transcriptomic landscape predictive of weak anti-tumor immunity. These findings are in agreement with previous results, demonstrating that RvD supplementation reduces cancer growth in experimental models of tumorigenesis [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, an impairment in the RvD pathway (biosynthesis and signaling) could be detrimental in cancer, since it is linked to poorer prognosis and associated with a transcriptomic landscape predictive of weak anti-tumor immunity. These findings are in agreement with previous results, demonstrating that RvD supplementation reduces cancer growth in experimental models of tumorigenesis [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 94%
“…We and others recently reported pre-clinical evidence that the stimulation of resolution is beneficial to counteract primary and metastatic neoplasia [ 9 , 10 , 11 , 12 , 13 ]. However, if and how resolution pathways are defective in cancer and influence tumorigenesis is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that AT-RvD1 inhibited the TGF-b1-induced epithelial to mesenchymal transition of A549 human lung adenocarcinoma epithelial cells, thus blocking tumor cell migration and metastasis [137]. In another model of lung adenocarcinoma in mice with an oncogenic Kras G12D mutation, AT-RvD1 decreased tumor growth and reduced the neutrophil-to-lymphocyte ratio, which is a marker for poor prognosis of cancer outcomes [138].…”
Section: Resolvinsmentioning
confidence: 77%
“…Various ω-3 metabolites of polyunsaturated fatty acids inhibit tumorigenic pathways; for example, the eicosapentaenoic acid metabolite ω-3,17,18-epoxide cascade activates anti-proliferation and pro-apoptosis pathways (85). Resolvins produced by LOX metabolites are effective inhibitors of tumor-derived inflammatory pathways (86). The cytosolic phospholipase A2-AA-COX-2 pathway is an important signaling pathway of inflammation, and some key factors of the pathway are associated with lung cancer.…”
Section: Lipid Metabolismmentioning
confidence: 99%